2011
DOI: 10.1143/jjap.50.07hc15
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Estimating the Location of the Drill-Bit During Horizontal Directional Drilling Using a Giant-Magnetostrictive Vibrator

Abstract: We study the inflated phase of two-dimensional lattice polygons, both convex and column-convex, with fixed area A and variable perimeter, when a weight μ t exp[−Jb] is associated with a polygon with perimeter t and b bends. The mean perimeter is calculated as a function of the fugacity μ and the bending rigidity J. In the limit μ → 0, the mean perimeter has the asymptotic behaviour t /4 √ A 1 − K(J)/(ln μ) 2 + O(μ/ ln μ). The constant K(J) is found to be the same for both kinds of polygons, suggesting that sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Propagation velocity of sand in previous studies is shown. [28][29][30][31] When sand is assumed to be solid or liquid, propagation velocity is shown. 26) Ultrasound irradiation can be applied to SAGD, it is effective to propagate widely.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Propagation velocity of sand in previous studies is shown. [28][29][30][31] When sand is assumed to be solid or liquid, propagation velocity is shown. 26) Ultrasound irradiation can be applied to SAGD, it is effective to propagate widely.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The thermal expansion coefficient of adhesive cobalt is larger than that of diamond, which causes the polycrystalline diamond layer to generate intergranular cracking and quickly reduces its structural strength. 1,[10][11][12][13][14][15] Although the impact resistance of the polycrystalline diamond layer has increased significantly in the supporting role of carbide, its inside residual stress causes the PDC to still be easy to peel-off under a large impact load, which will result in the rapid loss of its rock-breaking ability. [16][17][18][19][20] In this paper, we propose a new type of embedded PDC based on our previous research.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we propose a method for the monitoring and imaging of the water content in the rooting zone of plants using sound vibration. 1) Shallow underground imaging using the sound wave vibration has been already performed, and there are techniques using a shear horizontal wave, [2][3][4][5][6][7][8][9][10] an electromagnetic sound source, [11][12][13][14] a giant magnetostriction vibrator, [15][16][17] and an air-borne wave [18][19][20][21][22] have been developed. However, no research in which irrigation is controlled by measuring the water distribution in the rooting zone of plants using sound vibration has been performed yet.…”
Section: Introductionmentioning
confidence: 99%